Orchardists’ Needs for the Development of Technology and Innovation - Sayruamyat, Suwanna; Praneetvatakul, Suwanna; Vijitsrikamol, Kampanat; Potchanasin, Chakrit; Thamthanakoon, Nithicha; Pananurak, Piyatat (Journal of Business, Innovation and Sustainability (JBIS), 2022)
This article aims to summarize the situation of problem and barriers, and to explore the need for technology and innovation in the production of fruit orchards. The study analyzed by a survey of 295 farmers and data from in-depth interviews with 31 farmers following the 5-Whys concept. The results show that the most important problem is climate variability, which cause the problems of plant pathology, insect pest and low rate of flowering. For these reasons, fruit planters require to develop accurate climate forecasting technology at the field level, easy-to-use and inexpensive technology for soil quality and soil nutrient analysis, new varieties resistant to climatic variability, plant pathology and insect pest. Moreover, the size of the production area and the type of fruit trees affect different levels of the above problem indicating the different technological requirements. This study suggests that the developed technologies should vary to suit different both plated area and types of fruit trees leading to modern agriculture effectively.